PENGARUH MODIFIKASI KARBURATOR MENJADI INJEKSI TERHADAP KINERJA MESIN PADA MOTOR KLX 150 - Saputra, Mochammad Riza; Margianto; Nur Robbi (RING ME, 2023)
The need for comunity mobility to be able lo move from one place to another is increasing. Until now, the process of mixing air with gasoline in gasoline engines can be grauped into 2, namely the conventional system using a carburetor and the injection system. This study aims to compare engine performance based on fuel comsumption from engine that were originally convetional technology and then modified to the injection type. The methodology used is true experimental, with an analysis of variance model. From the research result, the power carburetor system at 10,000 rpm reaches 15.91 hp, and fuel consumption is 0.0334 kg/hp.hour, the efficiency is 0.4275%, while the injection system at 10,000 rpm reaches 17.82 hp, fuel consumption 0.0241 kg/hp.hour and 0.5924% efficiency. So that it can be concluded that the carburetor system lacks engine performance and burns a lot of wasted heat rafter than turning it into energy. The fogging injection system is more economical than the carburetor fogging system, it is evident in each test that the injection fogging system consumes less in every one working cycel.